Tindak Pidana Perdukunan Tinjauan Pasal 545, 546, 547 KUHP dengan Pasal 252 KUHP 2023 - Zafira, Aisyah (Taruna Law: Journal of Law and Syariah, 2024)
In Indonesia, the practice of black magic is not new. Although the practice is opposed to religion because it associates partners with God, it is still carried out by people who want to achieve their goals practically or harm someone. In the legal regulations in the Criminal Code, the practice of witchcraft is regulated in Articles 545, 546 and 547. In reality, this article is rarely used as a legal basis for the arrest or sentencing of black magic practitioners. The article on black magic has been discussed for a long time in the draft Bill of the Penal Code, there are many pros and cons about this article on shamanism which is called the’pasal santet’. In 2023 the new Penal Code was passed and the article on witchcraft was regulated in Article 252. with the legal research method, this research focuses on examining the normative law that applies in Indonesia with descriptive analysis until this research concludes that the act of shamanism is a disturbing thing, articles 545, 546, and 547 are considered inappropriate in dealing with this, so that article 252 is needed as legal certainty.